2017
DOI: 10.1038/emm.2016.153
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-derived microRNAs in cancer metabolism: possible implications in cancer diagnostics and therapy

Abstract: Malignant progression is greatly affected by dynamic cross-talk between stromal and cancer cells. Exosomes are secreted nanovesicles that have key roles in cell–cell communication by transferring nucleic acids and proteins to target cells and tissues. Recently, MicroRNAs (miRs) and their delivery in exosomes have been implicated in physiological and pathological processes. Tumor-delivered miRs, interacting with stromal cells in the tumor microenvironment, modulate tumor progression, angiogenesis, metastasis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
163
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(164 citation statements)
references
References 122 publications
0
163
0
1
Order By: Relevance
“…101 In addition, they serve as ideal vectors for the reprogramming of diseased cells in various pathological states, such as PE, since they have the ability to change the phenotype of the target cell though various signaling cascades and transfer of RNA. 102,103 Mesenchymal SCs (MSCs) are rich in their application as regenerative agents of damaged or diseased However the use of MSC-derived exosomes to treat PE has its challenges, due to the complexity of the pathogenesis of the disease. It is thus a prerequisite to determine the role of placenta-derived exosomes in the pathogenesis of PE through isolation and characterization of exosomal cargo and functional activity, and to understand the mechanism of biogenesis of placenta-derived exosomes in normal and PE pregnancies.…”
Section: Perspectives On Engineered Exosomes In Pe Therapeuticsmentioning
confidence: 99%
“…101 In addition, they serve as ideal vectors for the reprogramming of diseased cells in various pathological states, such as PE, since they have the ability to change the phenotype of the target cell though various signaling cascades and transfer of RNA. 102,103 Mesenchymal SCs (MSCs) are rich in their application as regenerative agents of damaged or diseased However the use of MSC-derived exosomes to treat PE has its challenges, due to the complexity of the pathogenesis of the disease. It is thus a prerequisite to determine the role of placenta-derived exosomes in the pathogenesis of PE through isolation and characterization of exosomal cargo and functional activity, and to understand the mechanism of biogenesis of placenta-derived exosomes in normal and PE pregnancies.…”
Section: Perspectives On Engineered Exosomes In Pe Therapeuticsmentioning
confidence: 99%
“…There are countless possibilities for exosome techniques both in cancer and neuro-psychiatric diseases. Thus, exosomes represent a key aspect in future molecular medicine [83,142].…”
Section: Resultsmentioning
confidence: 99%
“…But there is also the chance to use exosomes in molecularly targeted therapeutic approaches (Figure 4) [1,13,142]. As exosomes carry distinct surface markers, they can be detected by distinct target cells for cell to cell communication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, miRs have emerged as integral components of various biological processes, including cell proliferation, migration, differentiation, apoptosis and angiogenesis (4). It has been demonstrated that the altered expression of miR is associated with tumorigenesis and the progression of different types of cancer (5,6). By regulating multiple potential target genes, miR expression may lead to pathological changes in cells, ultimately contributing to the development of cancer (7).…”
Section: Introductionmentioning
confidence: 99%